2021
DOI: 10.1088/1361-6501/ac329e
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility investigation of rail monitoring by wheel-mounted acoustic emission technology using two-dimensional analytical contact acoustic nonlinearity model

Abstract: In an attempt to analyze the feasibility of a rail monitoring scheme with a wheel-mounted acoustic emission measurement method, a two-dimensional analytical spring model was proposed to interpret the interactions between acoustic waves and stationary wheel-rail contact interfaces. The spring model represents the coupling strength of the interfaces with their stiffness. It accommodates the environmental information of contact stiffness and the acoustic source information, such as the feature frequency and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Besides, the excitation current of the EMAE was set to sinusoidal signal with a frequency of 1 MHz. Recently researches had shown that the defect AE signals were mainly concentrated in [0.1 MHz, 1 MHz], but the AE signals will be attenuated after 0.8 MHz [30,31]. Therefore, in general, the mainly frequency distribution of AE signals was below 1 MHz, the excitation frequency was set to 1 MHz to avoid signal overlapping.…”
Section: Micro-deformation Analysis In Different Rail Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the excitation current of the EMAE was set to sinusoidal signal with a frequency of 1 MHz. Recently researches had shown that the defect AE signals were mainly concentrated in [0.1 MHz, 1 MHz], but the AE signals will be attenuated after 0.8 MHz [30,31]. Therefore, in general, the mainly frequency distribution of AE signals was below 1 MHz, the excitation frequency was set to 1 MHz to avoid signal overlapping.…”
Section: Micro-deformation Analysis In Different Rail Specimensmentioning
confidence: 99%
“…Device 6 were two receiving sensors (Model: VS900-RIC) and used to utilized to receive the signals from the specimen. Besides, the couplant was filled between the receiving sensors and the specimen, to reduce acoustic reflection and refraction [31]. The AE signals were acquired by the AE acquisition system (Device 8, Model: Vallen AMSY-6) with a sampling rate of 5 MHz.…”
Section: Experiments Producementioning
confidence: 99%
“…Considering its high sensitivity and dynamic detection without blind regions, AE technique has received considerable attention by the research community in the application of rail crack detection [5]. In such scenarios, AE transducers are generally attached to the rail surfaces and directly receive the transient bursts emitted from damaged materials, which contain abundant information associated with the growing cracks, such as the feature frequency characteristics [6]. However, the crack growth typically occurs when the trains are passing and the recorded crack signals are interfered with the strong mechanical noises from the wheel-rail interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, high-speed railway systems have made significant progress in the field of freight transport and passenger travel [1]. Meanwhile, with the heavy operation of the railway system, rail crack defects caused by the rolling contact fatigue are becoming more and more common [2].…”
Section: Introductionmentioning
confidence: 99%